Evolution of Economic Laws: A Comparative Analysis of Global Trends - Pandey, Prashant; Deepak, Deepak; Sakshi, Sakshi; Srivastava, Ratnesh Kumar; Tiwari, Priyadarshini; Uttam, Preeti (Journal of Neonatal Surgery, 2025)
This paper examines the evolution of economic rules in several spheres together with an analysis of main global trends affecting their development. Economic laws are dynamic and reacting to changes in political ideas, technical developments, and economic crises. This paper addresses the elements influencing the evolution of legal systems by means of a comparison between several economies, so revealing both commonalities and differences in this process. This work examines the economic study of law following its formalization in the middle of the 20th century by Chicago school scholars including Aaron Director, George Stigler, and Ronald Coase from classical economists such as Adam Smith and David Ricardo. It examines significant methodological foundations, including Richard Posner's approach, and how objections have motivated developments in disciplines including behavioural economics and game theory. Emphasizing the dual use of law and economics in predicting legal outcomes and influencing policy, the study guides its influence with efficiency—especially Pareto efficiency. Globally used all around the United States, Germany, India, and Africa, shows its adaptability. Emphasizing the field's changing and multidisciplinary character, the research finally addresses objections from challenges to neoclassical assumptions to ideas for more flexible models.